Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 12 Sequences and Series - 12.3 Analyze Geometric Sequences and Series - 12.3 Exercises - Mixed Review - Page 817: 77



Work Step by Step

Here, we have $\sum_{i=4}^{9} 4i^2=4 \sum_{i=4}^{9} i^2$ $=4(\sum_{i=1}^{9} i^2-\sum_{i=1}^{3} i^2)$ Use a summation formula such as: $\sum_{i=1}^{n} i^2=\dfrac{n(n+1)(2n+1)}{6}$ Now, $4(\sum_{i=1}^{9} i^2-\sum_{i=1}^{3} i^2)=4 \times (\dfrac{9(9+1)(2(9)+1)}{6}-\dfrac{3(3+1)(2(3)+1)}{6})=1084$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.